VELOCITY ANALYSIS USING N-TH ROOT STACK - Suprajitno Munadi; Pambudi Pambudi (Testing Center for Oil and Gas LEMIGAS, 1989)
The estimation of seicmic wave velocity in the subsurface is one of the most important process in seismic data processing. The result is very crucial for the conversion af seismic data fromtime section into depth section. The N-th Root Stack which has not been widely used in the industry in fact a powerful method for estimating seismic wave velocity from seicmic record. The method attenuates the background/random noise effectiviely which facilitates tre fitting of the velocity spectrum can be done anccurately. In addition, the noise is also effectivdy suppressed during the CDP stackins, yielding the clear inrim i doking amplitude Synthetic records have been used to demonstrate the effectiveness of the N-th Root Stack Comparison with the Delay and Sum method also demonstrate the superiority of the N-th Root Stack.